Preferences for timber species among value-added wood product manufacturers in Malaysia - Lim, Choon Liat (2017)
In the recent past, value-added wood products manufacturers in Malaysia have been increasingly using important wood materials to supplement the local resources. Although previously thought that the reducing supply and increasing cost of local wood resources is leading to increasing wood imports, these arguments have remained unsubstantiated. In fact, research investigating the attributes of sawn timber that influence its usage by the wood based manufacturers in Malaysia have been limited and unreported. Therefore, the objective of the study was to assess the attributes of sawn timber species for door, flooring and furniture manufacturers in Malaysia. Apart from identifying the success factors of the preferred species for particular wood products manufacturing, the study would also identify the general attributes that predetermines the success of the wood species selected in the manufacture of the three value-added wood products. The attributes explored were: cost, market/buyer preference, aesthetic quality, working properties, supply/availability, environmental friendly, product specification, durability, strength and hardness, and price premium for finished good. It is apparent that sawn timber attributes are important for many types of value-added product manufacturers in term of market opportunities and consumer preference. A questionnaire based survey was carried out in 2015 on 30 value-added manufacturer, in which there were ten manufacturers from each wood product category: door, floor and furniture. From each product category, 5 of the manufacturers relied on imported wood species, while the other 5 manufacturers used predominantly local wood species in their production. Such differentiation allowed for a constructive evaluation of the preferential usage of wood species in the various wood products categories. The respondents chosen were all export-oriented large-sized manufacturers, who had consented to participate in the study, located throughout Peninsular Malaysia. The study evaluated three aspects: the choice of sawn timber species for a particular types of wood products, the source of origin of sawn timber and the attributes of sawn timber that are perceived to be important in determining the choice of sawn timber species for a particular product . The result from the evaluation showed that the common local sawn timber species include Rubberwood (Hevea brasiliensis), Meranti (Shorea spp.), Merpauh (Swinntonia spp.), Merbau ( Intsia spp.) and Kempas ( Koompassia malaccensis) while, the imported timber species preferred by the value-added wood products manufacturers were White Poplar (Liriodendron tulipifera ), Oak (Quercus spp.), Cherry (Prunus spp.) and Pine ( Pinus spp.). The factor analysis on the ten attributes of sawn timber that affected its preferential usage were further simplified into 3 main groups: i) sawn timber properties ii) raw material sustainability and iii) consumer preference. Group 1 include variables such as working properties, aesthetic quality, durability and strength and hardness; Group 2 include variables such as environmental friendliness, supply/availability and price premium for finished good. Group 3 include variable such as product specification, cost and market preference. Although the choice of wood species used for particular application may differ, the general attributes that predetermines the wood species preferences for the manufacture of particular value-added wood products could be generalized. In this context, the results indicated that the cost, supply/availability, and market/buyer preference were among the most important factors influencing the selection of sawn timber species for the manufacturer of value-added wood products. This would seem to indicate that the wood products manufacturers appeared to emphasize on price stability, reliability of supply and preference of market/buyer. In other words, these manufacturers could not, or would not accept rapid price fluctuation, as considerations, in selecting their choice of sawn timber species. The results of the study has a far reaching implication on ensuring raw materials sustainability to ensure the continuous growth of the wood products industry in the country. As demonstrated in this study, wood species preferences are important criterion that must be taken into consideration on the wood raw materials supply management in the country.